2021
DOI: 10.3390/su13137351
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Power Management Strategy of Electric Vehicles Based Hybrid Renewable Energy

Abstract: This paper presents a straightforward power management algorithm that supervises the contribution of more than one energy source for charging a vehicle, even if the car is in motion. The system is composed of a wireless charging system, photovoltaic (PV) generator, fuel cell (FC), and a battery system. It also contains a group of power converters associated with each energy resource to make the necessary adaptation between the input and output electrical signals. The boost converter relates to the PV/FC, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…where K sys is the frequency characteristic constant of the system. Because there is a delay between frequency changes and power deviation, the transfer function for system frequency changes in terms of per unit frequency deviation can be determined by Equation (3) [29]:…”
Section: Power and System Frequency Deviationmentioning
confidence: 99%
See 1 more Smart Citation
“…where K sys is the frequency characteristic constant of the system. Because there is a delay between frequency changes and power deviation, the transfer function for system frequency changes in terms of per unit frequency deviation can be determined by Equation (3) [29]:…”
Section: Power and System Frequency Deviationmentioning
confidence: 99%
“…In [29], the authors conducted research for the control of island microgrids to reduce the frequency and power fluctuations and in [30] for intelligent frequency control for an AC microgrid or a combination of the particle swarm algorithm and fuzzy logic. In [31], the authors focused on the stability and control of the microgrid, which included a combination of microturbines, fuel cells and electrolyzers and was self-regulated by a fuzzy controller.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the design of an optimized PV system becomes difficult. Consequently, the development of efficient techniques to overcome these problems is of paramount importance [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, electricity generation from this resource is quite viable for a variety of uses. In particular, the rapid development of solar energy instruments gives a complete kit of tools that can be directly applied into the field of Electric Vehicles (EV) [3,4]. Several studies have suggested that photovoltaic cells can be used to cover EVs' surfaces to store a significant amount of electricity in the storage system [5,6].…”
Section: Introductionmentioning
confidence: 99%